2017
DOI: 10.1117/1.jbo.22.5.057001
|View full text |Cite
|
Sign up to set email alerts
|

No-core fiber-based highly sensitive optical fiber pH sensor

Abstract: The present work describes the fabrication and characterization of an optical fiber pH sensor using a sol–gel technique. The sensing head configuration is incorporated using a short section of no-core fiber, coated with tetraethyl orthosilicate and spliced at the end of a single mode fiber with a bulge. Different types of indicators (bromophenol blue, cresol red, and chlorophenol red) were used to achieve a wide pH range from 2 to 13. High sensitivities of the fabricated device were found to be 1.02 and ? 0.93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…15 Bhardwaj et al reported a no-core OFS using a sol-gel technique and three pH indicators to achieve a wide pH range, i.e., between 2 and 13. 18 The developed sensor showed a sensitivity of 1.02 and 0.93 nm pH À1 for acidic and alkaline solutions, respectively. However, the application of this type of sensor in the eld of civil engineering is still far from being ready for the market.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…15 Bhardwaj et al reported a no-core OFS using a sol-gel technique and three pH indicators to achieve a wide pH range, i.e., between 2 and 13. 18 The developed sensor showed a sensitivity of 1.02 and 0.93 nm pH À1 for acidic and alkaline solutions, respectively. However, the application of this type of sensor in the eld of civil engineering is still far from being ready for the market.…”
Section: Introductionmentioning
confidence: 91%
“…In recent years, several OFS functionalised with sol-gel membranes have been reported, including for pH sensing. [12][13][14][15][16][17][18] Pathak and Singh developed a down-tapered OFS for pH monitoring using three pH indicators in a sol-gel membrane with a maximum sensitivity of 0.49 dBm pH À1 . 14 Timbó et al also used a pH indicator (bromocresol purple) on a sol-gel matrix, resulting in a sensor with acceptable linearity between a pH of 4 and 10.…”
Section: Introductionmentioning
confidence: 99%
“…The development of OFS functionalized with OIH materials has already been reported for application in several fields, including biomedical [52], civil engineering [28,[62][63][64], and environment [48,56,65]. Bhardwaj et al [66] reported the development of an OFS for pH detection with different indicators, namely bromophenol blue, cresol red, and chlorophenol red, achieving a pH range between 2 and 13. A shift in resonance wavelength towards blue in alkaline solutions (−0.93 nm/pH) and a shift in resonance wavelength towards red in acidic solutions (1.02 nm/pH) were found.…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, various research on non-glass pH sensors [ 8 , 9 ] is gradually becoming a hot spot. Optical pH sensors recently drew increased attention from researchers and users for its stable measurement signal, ease of transport, strong anti-electromagnetic-interference properties, pollution-free nature, and other advantages [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%